Strategi Packing dan Branding Syariah sebagai Instrumen Penurunan Biaya Produksi UMKM - Fatmawati Sungkawaningrum; Alifia Choirun N; Kinanti Sayekti A; Sikta Aulia R (AMAL: Jurnal Ekonomi Syariah, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the national economy, but still face various challenges in production efficiency. One of the main challenges is managing production costs, both in the short and long term. This article analyzes how production costs in MSMEs can be controlled through packaging and branding training. The approach used is literature study and empirical observations of MSMEs that have taken part in this training. The research results show that packing training helps reduce operational costs by optimizing packaging materials and minimizing product damage. Meanwhile, effective branding increases product competitiveness and increases sales volume, thereby reducing production costs per unit in the long term. The conclusion of this research is that investment in packaging and branding training not only increases cost efficiency but also provides a competitive advantage for MSMEs in an increasingly competitive market. Therefore, continued support is needed from the government and related institutions to expand access to this training for MSMEs.